A six-time Ultraman winner and a normal heart: A case report. (4th February 2014) - Araújo, Claudio Gil Soares de; Belém, Luciano; Gottlieb, Ilan
Number of subjects currently participating in high-endurance aerobic exercise training regimens and competitions has substantially increased in recent years. While there is no doubt that regular exercise practice is fundamental for the maintenance of a good health, there have been reports of cardiac structural changes of subjects exposed to strenuous endurance physical exercise. This article reports a case of a 47-year-old male very successful sportsman—including being a six-time Ultraman winner—who has accumulated more than 50, 000 h of training and competition in his 35-year career, averaging 25–30 h/week. Despite this huge amount of aerobic exercise, about 25 times larger than typically recommended dose for health purposes (i.e. 75 min of vigorous exercise per week), no major abnormalities were detected in electrocardiograms (rest and maximal exercise), transthoracic echocardiogram, and magnetic resonance imaging. In fact, after this complete evaluation, his heart was found to be quite normal.